Analisis Gaya Bahasa Kiasan Cerpen “11:11 Bab Senja Bersayap” Karya Fiersa Besari (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The figurative language style of the short story 11:11 in the Winged Dusk chapter is the main study in this article. The short story Senja Berwing chapter 11:11 presents inner contact between characters and imagination and contains many positive moral messages and messages of humanity using beautiful language so that it attracts readers to read it. The purpose of this study is to find out what figurative language style is used by the writer and what meaning he wants to convey to the reader. Data collection techniques used in this study were (1) reading techniques, (2) listening techniques, and (3) note-taking techniques. Data analysis techniques are (1) identification, (2) classification, (3) interpretation, (4) description. This research study is focused on the analysis of figurative language style in the short story Senja Berwing chapter 11:11 by Fiersa Besari. The results of the research show that the figurative language style used in the short story 11:11 chapter of the Winged Senja by Fiersa Besari is simile, personification, and allegory. The type of figurative language that is mostly used in the Winged Twilight Chapter is personification figurative language.